Investigation of thermal stability and crystallization mechanism of Er0.03(GeTe)0.97 phase change material. (1st January 2023) - Gu, Han; Wu, Weihua; Xu, Shengqing; Zhou, Xiaochen; Shen, Bo; Zhai, Jiwei
Abstract: Er-doped GeTe thin films with different concentrations were prepared by magnetron co-sputtering technique. The chemical compositions of Er0.03 (GeTe)0.97 thin films were measured by energy dispersive spectroscopy. The difference between the phase transition behavior of Er0.03 (GeTe)0.97 and pure GeTe films was investigated by in-situ electrical measurements. The crystallization temperature, crystallization resistance and optical band gap of GeTe thin films obviously increase with the doping of Er elements. X-ray diffraction and x-ray photoelectron spectroscopy show that proper Er doping can inhibit grain growth and reduce grain size. The surface morphology of Er0.03 (GeTe)0.97 and pure GeTe films were observed by atomic force microscopy and it was found that the surface of the film becomes smoother after Er doping. The flatter surface of Er0.03 (GeTe)0.97 material means better interfacial properties and reliability. All the outcomes indicate that the proper doping of Er element can effectively improve the comprehensive performance of GeTe thin films for high thermal stability applications.